Analisa Proses Seleksi Operator pada PT. Dhanar Mas Concern Bandung - Hersa Dwi Yanuarso; Rinda Gusvita; Rohmah Helmikawaty (OPSI, 2020)
Employees or human resources are important assets in a company especially for textile industry. However, one of the important problems of the textile industry is the level of turnover. PT. Dhanar Mas Concern is an export-oriented textile company located in South Bandung which has a vision to be the best textile company with the most complete and best product in the world. In general, the person who controls these yarn and fabric making machine is called the operator (labor). The success of a company in managing the human resources is depend on the result of the selection process. So far the selection process for operators is carried out routinely every two times a week according to the needs of employees, due to hngh turnover rates. The high turnover rate is also a complaint of supervisors or team heads. The objective of the study is to determine how the selection process is conducted in textile company and the correlation between the the theory and the implementation in PT. Dhanar Mas Concern. The methodology research that used in this study is qualitative approach with descriptive research approach. This research shows that the selection process in PT. Dhanar Mas Concern met 7 (seven) of 8 (eight) stages which presented by William B. Werther Jr. and Keith Davis. The company overstepped the stage about interview with supervisors (user). The researcher suggests the company to implement the selection stages of interview with supervisors (user) cause the supervisor are the best informed of the technical aspects of the job. Supervisors interview may help to determine the extent of the applicants meet the company’s employment requirements.